Rosalinda Food Ordering Mobile Application - Diri, Muhammad Zairi Yasar; Nurezayana Zainal, (Applied Information Technology And Computer Science, 2023)
Rosalinda Food Ordering Mobile Application is an innovative solution developed to address the frustrations caused by traditional methods of ordering and serving customers at Restoran Rosalinda. Issues such as unreadable handwritten orders, miscommunication between customers and staff, and unnotified cook times are resolved through this online food ordering system. With just a few clicks, customers can place orders and make quick payments, resulting in faster service compared to long wait times during peak hours. Developed using the Prototyping Model methodology and built with Flutter technologies and Dart language, the user-friendly application improves the overall customer experience while reducing employee workload. By streamlining the ordering process and increasing efficiency, the application helps the restaurant save costs and deliver better service to its customers.